Kontribusi Peserta, Klaim dan Hasil Investasi Terhadap Surplus (Defisit) Underwriting Dana Tabarru’ Pada Perusahaan Asuransi Umum Syariah Di Indonesia Periode 2015-2019 - dalhlia tri anggraini (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2022)
The purpose of this study to test the effect of participant contributions, claim and investment returns to tabarru’ fund underwriting surplus (defisit). The type data in this study is secondary data with the population of sharia general insurance companies which listed on The Financial Services Authority as of December 31, 2019. The sample is selected by using purposive sampling method as many as 20 companies and data analysis techniques using descriptive statistics and panel data regression analysis with the tools Eviews ver. 11. The data’s period of this study is during 5 years (2015-2019). From the result of research indicate that participant contributions, claim and investment returns are affected significantly to tabarru’ fund underwriting surplus (defisit).